On the use of Sparse Principal Component Analysis and Robust: Selection Features of Maize Yield in Rural Tanzania - Mbukwa, Justine N.; Anjaneyulu, GVSR (MANECH Pblications, 2024)
Article published by MANECH Publications in the Journal of Engineering Mathematics and Statistics Volume 1 Issue 1